Modelling knowlesi malaria transmission in humans: Vector preference and host competence - Yakob, L; Bonsall, M; Yan, G; Bonsall, M (BioMed Central, 2010)
Background: Plasmodium knowlesi, a malaria species that normally infects long-tailed macaques, was recently found to be prevalent in humans in Southeast Asia. While human host competency has been demonstrated experimentally, the extent to which the parasite can be transmitted from human back to mosquito vector in nature is unclear. Methods. Using a mathematical model, the influence of human host competency on disease transmission is assessed. Adapting a standard model for vector-borne disease transmission and using an evolutionary invasion analysis, the paper explores how differential host competency between humans and macaques can facilitate the epidemiological processes of P. knowlesi infection between different hosts. Results. Following current understanding of the evolutionary route of other human malaria vectors and parasites, an increasing human population in knowlesi malaria endemic regions will select for a more anthropophilic vector as well as a parasite that preferentially transmits between humans. Applying these adaptations, evolutionary invasion analysis yields threshold conditions under which this macaque disease may become a significant public health issue. Conclusions. These threshold conditions are discussed in the context of malaria vector-parasite co-evolution as a function of anthropogenic effects. © 2010 Yakob et al; licensee BioMed Central Ltd.